ANALISIS PERSEPSI GURU TERHADAP KESESUAIAN CAPAIAN PEMBELAJARAN PAI DALAM KURIKULUM MERDEKA DI SD - Lulu Saputri; Suci Mulia; Riska Nuraini; Abdurrahmansyah Abdurrahmansyah (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study explores how Islamic Religious Education teachers interpret the relevance of the Learning Outcomes in the Independent Curriculum to the real-life situations of elementary school students. The main focus includes teachers' level of understanding, the suitability of the material to student characteristics, and various challenges and solutions in its implementation. Using a descriptive qualitative approach, data was collected from teachers using in-depth interviews and documentation studies, which were then validated through source triangulation. The findings indicate that teachers view the Learning Outcomes as phase-based competency guidelines that offer flexibility in developing aspects of knowledge, attitudes, and skills in an integrated manner. Although the Learning Outcomes are considered capable of encouraging student engagement, in practice, obstacles still exist in the form of limited facilities and infrastructure, limited internet access, and gaps in teacher competency and differences in student comprehension. To address these issues, educators need to optimize the use of simple learning media, revise teaching methods, and strengthen personal guidance and collaboration between teachers. Ultimately, this study concludes that the successful implementation of the Islamic Religious Education Learning Outcomes does not rely solely on the curriculum but is highly dependent on improving the quality of teacher professionalism accompanied by the provision of adequate facilities and infrastructure. ABSTRAK Penelitian ini mengeksplorasi tentang bagaimana guru Pendidikan Agama Islam (PAI) memaknai relevansi Capaian Pembelajaran (CP) dalam Kurikulum Merdeka terhadap kondisi nyata siswa sekolah dasar. Fokus utamanya mencakup tingkat pemahaman guru, kesesuaian materi dengan karakteristik anak didik, serta berbagai tantangan dan solusi dalam implementasinya. Melalui pendekatan kualitatif deskriptif, data dihimpun dari guru dengan menggunakan teknik wawancara mendalam dan studi dokumentasi, yang kemudian divalidasi melalui triangulasi sumber. Temuan menunjukkan bahwa guru memandang CP sebagai pedoman kompetensi berbasis fase yang menawarkan fleksibilitas dalam mengembangkan aspek pengetahuan, sikap, dan keterampilan secara terintegrasi. Meskipun CP dianggap mampu mendorong keaktifan siswa, faktanya di lapangan masih ditemukan hambatan berupa keterbatasan sarana dan prasarana, kendala akses internet, serta adanya kesenjangan kompetensi guru maupun perbedaan daya tangkap siswa. Untuk menyelesaikan persoalan tersebut, para pendidik perlu mengoptimalkan penggunaan media pembelajaran sederhana, merevisi metode mengajar, serta memperkuat bimbingan personal dan kolaborasi antar guru. Pada akhirnya, studi ini menyimpulkan bahwa keberhasilan penerapan CP PAI tidak hanya bertumpu pada kurikulum semata, melainkan sangat bergantung pada peningkatan kualitas profesionalisme guru disertai dengan penyediaan sarana prasarana yang memadai.